An Asymmetric‐Electrolyte Zn−Air Battery with Ultrahigh Power Density and Energy Density. Issue 4 (18th December 2017) - Cai, Pingwei; Li, Yan; Chen, Junxiang; Jia, Jingchun; Wang, Genxiang; Wen, Zhenhai
Abstract: Zn−air batteries have attracted enormous research interest, driven by the promise for vehicle propulsion owing to their advantages of high‐level safety, low cost, and high specific energy density. Here, we report an asymmetric‐electrolyte Zn−air battery with acid catholyte and alkaline anolyte separated by a bipolar membrane. We demonstrate that the as‐designed Zn−air battery, thanks to the as‐formed concentration cell, can deliver a maximum power density of 380 mW cm −2 and a specific energy density of 1522 Wh kg −1 with an open‐circuit voltage of 2.25 V. The as‐proposed Zn−air battery performance is superior to the conventional Zn−air battery in terms of these pivotal performance parameters. Abstract : Battery with potential : An asymmetric‐electrolyte Zn−air battery is developed with a bipolar membrane separating the acidic catholyte and alkaline anolyte, which exhibits an ultrahigh power density of 380 mW cm −2 and an energy density of 1522 Wh kg −1 with an open circuit voltage of 2.25 V. The significantly improved performance of the as‐proposed Zn−air battery can be attributed to the conversion of electrochemical neutralization energy to electrical energy.